Ajuste da lâmina de irrigação no desempenho agronômico da cultura do milho - Chechi, Leonardo (2016)
As the water stress is one of the main causes for the low maize yield in Brazil, the presented study aimed to evaluate the yield components, grain yield and the water use efficiency of maize crop submitted to different ways of irrigation depth adjustment and validate the “Lâmina” worksheet to recommend irrigation in this crop. The treatments applied were: non-use of irrigation (control); irrigation depth adjustment provided by” Lâmina” worksheet (Lâmina); soil moisture equivalent to actual capacity of water in the soil at 55% of the total soil water capacity (55% ACW); and soil moisture equivalent to 100% of the field capacity (100% FC). The experimental design was a randomized block design with four replications, each experimental unit consists of a plot 3 m wide and 3 m long. The variables analyzed were water applied, dry matter, number of ears per plant, number of kernel rows per ear, number of kernels per row, number of kernels per ear, thousand kernels weight, grain yield and liters of water per kilogram of grains produced. Grain yields were similar between irrigated treatments, showing significant differences compared to the control. The treatments Lâmina and 55% CRA showed the best results for water use efficiency and yield components. The Lâmina treatment used the least amount of water, with high yields, contributing to the rational water use in irrigated agricultural systems.